Biochemical analysis of the living human vitreous. (19th April 2016) - Kokavec, Jan; Min, San H; Tan, Mei H; Gilhotra, Jagjit S; Newland, Henry S; Durkin, Shane R; Grigg, John; Casson, Robert J
Abstract: Background: To date, our understanding of the biochemical composition of the living human vitreous relies on extrapolations from animal or human post‐mortem studies. Methods: This was a cross‐sectional study of vitreous samples from 27 individuals scheduled for retinal surgery within a tertiary hospital. From each vitreous sample, the concentrations of sodium, potassium, chloride, calcium, magnesium, glucose, lactate, β‐ hydroxybutyrate, copper, zinc, selenium, iron, ferritin and transferrin and osmolality were measured. Perioperative serum samples were also obtained for comparison. Results: The following vitreous mean ± standard deviation (95% confidence interval of the mean) was observed for each analyte: sodium, 146.7 ± 3.3 (145.4–148.0) mmol/L; potassium, 5.73 ± 0.86 (5.39–6.08) mmol/L; chloride, 121.6 ± 2.6 (120.6–122.7) mmol/L; calcium, 1.128 ± 0.518 (0.923–1.333) mmol/L; magnesium, 0.900 ± 0.158 (0.838–0.962) mmol/L; glucose, 2.97 ± 0.98 (2.58–3.36) mmol/L; lactate, 3.97 ± 1.09 (3.54–4.40) mmol/L; osmolality, 289.5 ± 6.9 (286.6–292.5) mOsm/kg; BOHB, 0.0937 ± 0.0472 (0.0750–0.1124) mmol/L; copper, 0.519 ± 0.269 (0.412–0.625) µmol/L; zinc, 1.95 ± 1.09 (1.52–2.38) µmol/L; selenium, 0.1035 ± 0.0276 (0.0923–0.1146) µmol/L; iron, 3.11 ± 1.40 (2.56–3.66) µmol/L; ferritin, 19.5 ± 10.3 (15.5–23.6) µg/L; transferrin, 0.0878 ± 0.0526 (0.0670–0.1086) g/L. Vitreous biochemistry was not significantly different between male and female participants. Vitreous biochemistry was significantly different between non‐diabetic and diabetic participants. Vitreous biochemistry was significantly different from the vitreous substitute BSS Plus (Alcon, USA). The vitreous extracted from living humans was markedly different from the commonly reported reference values obtained from animal studies. Conclusions: The current data provide hitherto unavailable information about the biochemical composition of the living human vitreous.